2006
DOI: 10.1007/s11248-005-4024-3
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Determination of Zygosity in Transgenic Rice by Real-time PCR Does Not Require Standard Curves or Efficiency Correction

Abstract: A number of quantitative, real-time PCR methods have been developed for determining transgene copy numbers in plants. Here, we demonstrate that the Roche LightCycler system can be used to determine the zygosity of transgenic lines without the use of standard curves or efficiency correction calculations. We have developed a duplex PCR assay which permits the determination of zygosity, relative to a calibrator sample, in transgenic rice lines containing the gene for a viral glycoprotein. Our data demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Traditionally, T 1 plants are screened for zygosity by a time-consuming segregation analysis of their T 2 progeny, which necessitates growing the T 1 plant lines to maturity for the collection of their seeds to be germinated on selection media for screening. Using quantitative real-time PCR allows relative quantification of gene copy number, and hence can be used to determine zygosity (Bubner and Baldwin 2004;Ji et al 2005;Prior et al 2006;Shitara et al 2004;Tesson et al 2002). In this investigation, the homozygous and hemizygous transgenic papaya lines were distinguishable by real-time PCR method for determining zygosity.…”
Section: Discussionmentioning
confidence: 89%
“…Traditionally, T 1 plants are screened for zygosity by a time-consuming segregation analysis of their T 2 progeny, which necessitates growing the T 1 plant lines to maturity for the collection of their seeds to be germinated on selection media for screening. Using quantitative real-time PCR allows relative quantification of gene copy number, and hence can be used to determine zygosity (Bubner and Baldwin 2004;Ji et al 2005;Prior et al 2006;Shitara et al 2004;Tesson et al 2002). In this investigation, the homozygous and hemizygous transgenic papaya lines were distinguishable by real-time PCR method for determining zygosity.…”
Section: Discussionmentioning
confidence: 89%
“…The q-RT-PCR strategy has already proved useful for quantifying the transgene copy number (Ingham et al 2001;Batista et al 2008). However, in previous works a single copy gene was selected as reference gene in a relative q-RT-PCR (German et al 2003;Prior et al 2006). Bradeen et al (2009) showed a high correlation between the transgene quantification obtained using both a single copy gene (Urease) and a double copy gene (EF-1).…”
Section: Discussionmentioning
confidence: 97%
“…This adaptation of PCR allowed an easier quantification of target sequences [6,7]. Different techniques were developed and compared for these quantitative assays [8][9][10][11][12]. As more transgenic traits were commercialized, which in some cases contained the same gene constructs, the specificity of the assays had to be increased by the development of eventspecific detection assays [13,14].…”
Section: Introductionmentioning
confidence: 99%